2014
DOI: 10.1371/journal.pone.0111103
|View full text |Cite
|
Sign up to set email alerts
|

Menin: A Tumor Suppressor That Mediates Postsynaptic Receptor Expression and Synaptogenesis between Central Neurons of Lymnaea stagnalis

Abstract: Neurotrophic factors (NTFs) support neuronal survival, differentiation, and even synaptic plasticity both during development and throughout the life of an organism. However, their precise roles in central synapse formation remain unknown. Previously, we demonstrated that excitatory synapse formation in Lymnaea stagnalis requires a source of extrinsic NTFs and receptor tyrosine kinase (RTK) activation. Here we show that NTFs such as Lymnaea epidermal growth factor (L-EGF) act through RTKs to trigger a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 41 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…The downregulation of GAP43 is associated with an EGFR inhibitor treatment and development (S. M. Liu et al, ). EGF and EGFR show neurotrophic and protective functions and promote axon growth and synapse formation (Flynn et al, ; Gibson & Tolbert, ; Hermann et al, ; Iwakura et al, ; Peng et al, ). However, GAP43 is a key protein that regulates the intrinsic neurite regenerative ability of neurons that is expressed at a low level in adult primary sensory neurons (Dubovy, Klusakova, Hradilova‐Svizenska, & Joukal, ; Qiao, Cong, Li, Li, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of GAP43 is associated with an EGFR inhibitor treatment and development (S. M. Liu et al, ). EGF and EGFR show neurotrophic and protective functions and promote axon growth and synapse formation (Flynn et al, ; Gibson & Tolbert, ; Hermann et al, ; Iwakura et al, ; Peng et al, ). However, GAP43 is a key protein that regulates the intrinsic neurite regenerative ability of neurons that is expressed at a low level in adult primary sensory neurons (Dubovy, Klusakova, Hradilova‐Svizenska, & Joukal, ; Qiao, Cong, Li, Li, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional strategies produce limited relief of sensory dysfunction (Dugan & Sagen, 2015). Thus, the and synapse formation (Flynn et al, 2014;Gibson & Tolbert, 2006;Hermann et al, 2000;Iwakura et al, 2011;Peng et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, we have demonstrated that CM serves as an extrinsic source of neurotrophic factors required for the postsynaptic expression of excitatory nAChRs in Lymnaea neurons (Xu et al, 2009;Flynn et al, 2014). To determine if the SrcI-induced perturbation of synapse formation was due to a change in the functional expression of postsynaptic nAChRs, single LPeD1 neurons were plated in CM or CM + SrcI (5 µM) overnight, for 14-18 h (Figure 2).…”
Section: Sfk Inhibition Does Not Affect the Postsynaptic Expression Omentioning
confidence: 90%
“…We have previously shown that excitatory synapse formation between soma-soma pairs of individually identified L. stagnalis neurons requires an extrinsic source of neurotrophic factors (supplied by CM). More specifically, excitatory synapse formation between the presynaptic neuron VD4 and the postsynaptic neuron LPeD1 relies upon activity-induced calcium influx in LPeD1, activation of the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) cascade, and expression of the transcription factor, Lymnaea menin, which are required for the expression of excitatory nAChRs (Xu et al, 2009;Flynn et al, 2014). Without neurotrophic factors, the nAChR phenotype remains inhibitory by "default" (Xu et al, 2009).…”
Section: Sfks Are Required For Soma-soma Synapse Formationmentioning
confidence: 99%